1980
DOI: 10.1093/bja/52.10.1027
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cortisol Concentrations During Caesarean Section

Abstract: The effects of extradural and general anaesthesia on the adrenocortical response to elective or emergency Caesarean section were studied in 72 patients. Maternal plasma concentrations of cortisol were measured before surgery, at delivery, and 30 and 60 min after skin incision. Umbilical vein and artery plasma cortisol concentrations at delivery were determined also. Maternal plasma cortisol concentrations in patients receiving extradural anaesthesia did not change significantly from control at any of the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Although maternal stress response was affected, the stress response in the fetus was not influenced by the use of spinal anesthesia in pregnant women with different body height in our study. This is similar to previous findings that fetal stress response is not affected by the type of anesthesia [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although maternal stress response was affected, the stress response in the fetus was not influenced by the use of spinal anesthesia in pregnant women with different body height in our study. This is similar to previous findings that fetal stress response is not affected by the type of anesthesia [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…Pain relief could suppress the release of stress hormones during surgery [ 25 ]. Spinal and epidural anesthesia have been shown to reduce the maternal stress response during cesarean section compared with general anesthesia [ 26 , 27 ]. In the present study, our results indicated that the increase of maternal cortisol level in the taller group was significantly greater than that in the shorter group at end of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, important to assess fetal cortisol levels and thus to try to understand which factors influence its relase. Namba et al [25] reported that the umbilical vein cortisol concentration was unaffected by the anesthetic method used; our own results agree with those of other authors [6,7] who demonstrated that umbilical vein cortisol concentrations are higher with epidural anesthesia (higher stress response) than with general anesthesia.…”
Section: Discussionsupporting
confidence: 92%
“…Parturition is characterized by a hormonal profile that is altered by obstetric intervention. Women who deliver vaginally have higher plasma levels of cortisol (Namba, Smith, Fox & Challis, 1980), β-endorphin (Goebelsmann, Abboud, Hoffman & Hung, 1984), oxytocin (Vasicka, Kumaresan, Han & Kumaresan, 1978), and norepinephrine and epinephrine (Irestedt, Lagercrantz, Hjemdahl, Hagnevik & Belfrage, 1982) at the time of delivery than women who deliver via cesarean with an epidural. Moreover, physiological differences between deliveries with and without obstetric intervention persist during the postpartum period (Nissen, Uvnas-Moberg, Svensson, Stock, Widstrom & Winberg, 1996; Zanardo, Nicolussi, Carlo, Marzari, Faggian, Favaro & Plebani, 2001).…”
Section: Discussionmentioning
confidence: 99%